(untitled) (Biological Sciences - PJSIR, 2010)
Aphids and their natural enemies were enumerated on 11 rose cultivars at weekly basis during the year 2005, at PMAS-Arid Agriculture University, Rawalpindi, Pakistan. Rose plants were found to be colonized by rose aphid (Macrosiphum pachysiphon), potato aphid (Macrosiphum euphorbiae, Rhodobium porosum), 7-spotted lady bird beetle (Coccinella septempunctata), syrphid fly (Episyrphis balteatus) and Aphidius rosae. Significantly, greater aphid populations were observed on the cultivar Blumonia than on other varieties. Higher percentage of parasitism and predation were observed on the cultivars, Good News and Golden Master, respectively.